Indie Weerbaar Polemic and the Radicalization of Sarekat Islam (1917-1918) - Miftahul Habib Fachrurozi (Indonesian Historical Studies, 2020)
This article analyses the polemic relationship between the formation of Indie Weerbaar and the radicalization of the Sarekat Islam. The organization later protected the Dutch East Indies from the effects of the First World War. The support from Sarekat Islam initiated  polemics with left groups within the Sarekat Islam. This article was written using the historical method. It emphasizes on the using of primary sources in the form of writing records from some prominent figures of Sarekat Islam. The results show that the Sarekat Islamdecentralization policy implemented by the Governor-General of Idenburg resulted in the organization's leadership losing control of its agencies. Abdoel Moeis' involvement in the Indie Weerbaar committee triggered a polemic against leftist figures in Sarekat Islam, especially Semaoen. Semaoen managed to take advantage of the formation polemic of Indie Weerbaar to increase his influence and popularity. Semaoen even succeeded in influencing the Sarekat Islam congress participants to support more radical organizational policies such as the labor movements. In other hand, Semaoen also succeeded in influencing other Sarekat Islam leaders, including Tjokroaminoto, to become more radical through the organization of Radicale Concentratie in Volksraad. Thus, it can be seen that the polemic on the formation of Indie Weerbaar led to the radicalization of the Sarekat Islam movement.